Competitiveness of agrifoods in Central American and Caribbean countries in the context of trade liberalization - Rodrigues, Mónica (CEPAL SantiagoCL, 2003)
Evaluates aspects of ex-post competitiveness; trade specialization; the dynamics of import markets; the main competitor countries; and, trade protection in the six Central American and eight Caribbean countries and the main destination markets, the European Union and the United States.